Comparison of underwater electrical wire explosions with large and small capacitors charged to a same energy - Li, Liuxia; Qian, Dun; Liu, Zhigang; Zou, Xiaobing; Wang, Xinxin (Physics of plasmas, 2020)
In order to investigate the effect of the current rise rate on the underwater electrical wire explosion (UEWE), two pulsed sources were used. One pulsed power source used an energy-storage capacitor of 1 μF while the other used a 200 μF capacitor. These two capacitors were charged to the same energy. The ratio of the current rise rate was about 11 for the UEWEs using these two pulsed sources at the same stored energy. In addition to the rise rate of the current, the wire resistance played an important role in affecting the energy deposition when it was comparable or even lower than the circuit resistance. The experimental results indicated that different capacitors may also lead to different discharge modes, even under the same energy storage and using the same size copper wire. It was found that the deposition energy, deposition power, the deposition ratio, and the discharge mode may influence the shock wave.